An Optimal Exchange Rate Peg in a World of General Floating - Flanders, M. June; Helpman, Elhanan (Review of Economic Studies, 1979)
M. June Flanders, Elhanan Helpman; An Optimal Exchange Rate Peg in a World of General Floating, The Review of Economic Studies, Volume 46, Issue 3, 1 July